The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1071/mf96131
|View full text |Cite
|
Sign up to set email alerts
|

Farm ponds in New South Wales, Australia: relationship between macrophyte and phytoplankton abundances

Abstract: The physical, chemical and biological characteristics of 65 farm ponds in the Northern Tablelands and Central Western Slopes regions of New South Wales, Australia, were similar to those recorded for Australian ponds in other studies. The strongest single relationship between physico-chemical characteristics and biological characteristics was for high abundance of phytoplankton, low abundance of macrophytes, high turbidity, and high nutrient concentrations in ponds on granitic soil. Variation among the ponds wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Casanova et al (1997) also have reported the co-occurrence of high macrophyte and phytoplankton biomass in a number of farm dams in New South Wales, Australia. It is possible that the nutrient-enriched mesocosms in Victoria Park Lake were in a transitional phase, on the way to ultimate dominance by phytoplankton; however, this would seem unlikely, given that no deleterious effects of nutrient enrichment were detected on any aspect of the performance of the submerged angiosperms.…”
Section: Effects Of Nutrient Enrichment: Phytoplankton and Epiphytesmentioning
confidence: 91%
“…Casanova et al (1997) also have reported the co-occurrence of high macrophyte and phytoplankton biomass in a number of farm dams in New South Wales, Australia. It is possible that the nutrient-enriched mesocosms in Victoria Park Lake were in a transitional phase, on the way to ultimate dominance by phytoplankton; however, this would seem unlikely, given that no deleterious effects of nutrient enrichment were detected on any aspect of the performance of the submerged angiosperms.…”
Section: Effects Of Nutrient Enrichment: Phytoplankton and Epiphytesmentioning
confidence: 91%
“…High nutrient conditions often lead to high biogenic turbidities (phytoplankton dominance) (e.g. Casanova et al, 1997). This suggests that at intermediate salinities, wetlands subject to episodic rainfall with moderate to high nutrient levels, may be prone to phytoplankton blooms (Fig.…”
Section: Implications For the Formation And Dominance Of Ecological Rmentioning
confidence: 98%
“…Results of a survey of farm dams in New South Wales indicate that aquatic plant communities are less diverse and abundant where Ž . cyanobacterial blooms occur Casanova et al, 1997 . This phenomenon is well supported by Northern Hemisphere studies in which the decline in submerged plant abundance has been attributed to shading of sub-Ž merged plants by algae in the water column Phillips et . al., 1978;Moss, 1991;Moss et al, 1996 .…”
mentioning
confidence: 87%
“…Ž . cm Casanova et al, 1997 . A shade control 20% , assumed to produce similar light attenuation to the turbidity in the cultures, and a culture solution control were added to the low density experiment to control for Ž .…”
Section: Characteristics Of the Culture Solutionsmentioning
confidence: 97%